ELECTRON AND PHOTON-STIMULATED DESORPTION FROM PHYSISORBED CO FILMS - Siller, L; Laitenberger, P; Palmer, R; Bennett, S; Foord, J; Macdonald, M (1995)
We have investigated photon stimulated desorption (PSD) and electron stimulated desorption (ESD) from CO films physisorbed on graphite and Pt(1 1 1) at monolayer coverages, with photon and electron energies in the range 13-35 and 0-70 eV, respectively. The C + ion yields in PSD from the two substrates show remarkable similarities. Therefore, we conclude that the CO dissociation proceeds mainly via direct molecular excitation processes. In ESD from CO/graphite the energy dependences of the C -, O -, C + and O + signals exhibit a variety of distinct thresholds and enable us to identify the desorption processes involved. A comparison of the PSD and ESD results provides further evidence for the direct nature of the desorption process in this model system. © 1995.